Numerical Simulation for Identifying Stress During Borehole Drilling Process - Jian Tan; Yanfeng Geng; Xuesheng Liu (Shock and Vibration)
How to identify the stress generally in coal seam during borehole drilling process is a hot topic. In engineering, to obtain the stress state by drilling torque is very necessary. This study intends to obtain the stress state and machine drilling torque by numerical simulations. Finite element method (FEM) is employed to simulate the dynamical drilling process, considering variations in coal mechanical properties and drilling torque. Results show that the stress in coal seam is positively correlated with drilling torque and coal modulus of elasticity, with a notable inflection point in stress variation at a drilling depth of approximately 13 m. Two fitting relationship formula between stress and torque, elastic modulus, and drilling depth, in the range from 0 to 13 m and exceeding 13 m, were obtained. The study provides an inversion identification approach by monitoring drilling torque, and it is hopeful to be used for early warning rock burst during pressure relief by borehole drilling.